2012
DOI: 10.1063/1.4751344
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functional properties of CaCu3Ti4O12 thin films

Abstract: In this work, electric transport properties of CaCu 3 Ti 4 O 12 (CCTO) thin films were investigated for resistive switching, rectifying and gas sensor applications. Single phase CCTO thin films were produced by polymeric precursor method (PPM) on different substrates and their electrical properties were studied. Films produced on LNO/Si substrates have symmetrical non-ohmic current-voltage characteristics, while films deposited on Pt/Si substrates have a highly asymmetrical non-ohmic behavior which is related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…19,20 The materials were first crushed and then pelletized via uniaxial (40 kN for 2 min) and isostatic (1000 kN for 2 min) pressing. The pellets were sintered in air (P O 2 = 0.21 bar) for 24 h at 1000 1C (the heating and cooling rate was 3 1C min À1 ).…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…19,20 The materials were first crushed and then pelletized via uniaxial (40 kN for 2 min) and isostatic (1000 kN for 2 min) pressing. The pellets were sintered in air (P O 2 = 0.21 bar) for 24 h at 1000 1C (the heating and cooling rate was 3 1C min À1 ).…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Several studies have shown that this perovskite can exhibit a dielectric permittivity of about 10 4 -10 5 for temperatures ranging from 100 K to 600 K without undergoing any phase transition [2,4,5]. On the other hand, non-linear current-voltage profiles have also been reported in ceramics [6], thin films [7,8] and recently in nanostructures [9] which are attributed to the conductivity on the film/metalelectrode interface and/or grain boundary mechanisms [10,11]. These properties make this material a promising candidate for applications in electronic devices such as capacitors, random access memories, microwave devices, and sensors [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…In general, a resistive switch can attain different resistance states which are controlled by the polarity or magnitude of an applied bias resulting in pinched hysteretic I–V profiles . In recent years, resistive switching has been reported for various classes of materials ranging from sulfides (e.g., Cu 2 S, Ag 2 S) to binary oxides (e.g., TiO 2 , SiO 2 , CuO, NiO, CoO, Fe 2 O 3 , MoO, VO 2 ) over to complex oxides (e.g., SrTiO 3‐δ , (La , Sr)MnO 3 , (Pr,Ca)MnO 3 , BaTiO 3 , (La,Sr)(Co,Fe)O 3 , CeCu 3 Ti 4 O 12 ) . Among those the most extensively studied switching oxides are already processed in today's semiconductor industry as gate oxides like SrTiO 3‐δ , SiO 2 , TiO 2‐δ , Ta 2 O 5‐δ or HfO 2‐δ.…”
Section: Introductionmentioning
confidence: 99%